Online Learning: How It Affects the University Structure and Economics. Panel discussion - Martin Carnoy; Yaroslav Kuzminov (Вопросы образования, 2015)
A panel discussion on online learning was held at National Research University—Higher School of Economics on June 16, 2015. The scenario included three main topical units: how online learning affects the education structure; incurred changes to tuition fees and cash flows; promising areas of online learning research. Particularly, the agenda embraced the following questions: How efficient is online learning? What benefits does it provide to its players (institution, teachers, and students)? What risks are there for online learning players (institution, students)? Who has a demand for online learning? How does distribution of online learning affect the global and national education systems and organization of universities? Will Russian universities introduce the practice of replacing conventional courses with massive open online courses (MOOC)? Will there be any limitations to such practice (e. g. will students only be able to choose MOOC for general subjects but not for field-specific disciplines? will they be able to choose from OpenEdX courses only)? How introduction of this practice will affect the organization of the learning process and the level of teaching load? Will replacement of conventional courses with MOOC result in job cuts? Can the MOOC phenomenon give rise to discrimination between cheap online and elite classroom education? How do MOOC change the education market? Is MOOC distribution increasing the ternational competition between universities? How will tuition fees be affected?